Anti reflective coating for silicon solar cells - Білоус, М.Г.; Ледовських, В.М. (Proceedings of National Aviation University (archive), 2009)
In the given work results on research of an opportunity of use antireflection coverings (ARC) converter photo-electric as coverages on a basis, received are resulted at the help liquid- face processes with their subsequent formation by a method centrifugation and high-temperature heat treatment. It is shown, that such АRC meet the basic requirements and behind the characteristics do not concede to the coverings received by other technological processes. The offered technology essentially easy and more economically in comparison with other ways, easily adapts up to requirements of industrial production and consequently is perspective for wide implementation.